PEMBERDAYAAN GABUNGAN KELOMPOK TANI DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI PETANI - Dewi Maryam; Shonhaji Shonhaji; Fauzi Fauzi; Lutfi Zaimuddin; Tontowi Jauhari (Agros Journal of Agriculture Science, 2023)
Empowerment in the field of agriculture is one of the important sectors in Indonesia's development efforts to combat poverty. According to the regulations of the Ministry of Agriculture, farmers are organized and structured within farmer groups in each hamlet and farmer group cooperatives (Gapoktan) at the village level. This study aims to obtain a deep understanding of the empowerment activities in the "Gapoktan Rukun Agawe Sentosa" cooperative and to analyze the stages of economic empowerment in the "Gapoktan Rukun Agawe Sentosa" cooperative in improving the welfare of farmers. This study is a qualitative research. Data collection techniques include interviews, documentation, and observation. The results of the study show that economic activities carried out by the cooperative include providing capital, implementing plantation, agriculture and livestock programs, handling livestock waste, and building cooperation with other parties. Every community empowerment activity needs to be based on appropriate work strategies for successful achievement of desired goals. Empowerment activities are carried out through three stages, starting from the awareness stage, capacity building stage, and empowerment stage. This forms the basis for the empowerment strategy in the "Gapoktan Rukun Agawe Sentosa" cooperative in Pekon Wonoharjo to improve the economic welfare of the community.INTISARIPemberdayaan pada bidang pertanian merupakan salah satu sektor penting pembangunan di Indonesia dalam upaya pemberantasan kemiskinan. Berdasarkan peraturan Mentri Pertanian, petani diatur dan ditata dalam wadah kelompok tani di tiap dusun dan gabungan kelompok tani (Gapoktan) di tingkat desa. Penelitian ini bertujuan memperoleh pemahaman yang mendalam mengenai kegiatan pemberdayaan pada Gapoktan rukun agawe sentosa serta untuk menganalisis tahapan pemberdayaan ekonomi pada Gapoktan rukun agawe sentosa dalam meningkatkan kesejahtraan petani. Penelitian ini merupakan penelitian kualitatif. Teknik pengumpulan data menggunakan metode interview dokumentasi, dan observasi. Dari hasil penelitian diketahui bahwa kegiatan ekonomi yang dilakukan diantaranya Gapoktan berfungsi sebagai sarana penyedia modal, menjalankan program perkebunan, pertanian dan peternakan, berperan dalam penanganan limbah ternak serta membangun kerjasama dengan pihak lain. Setiap kegiatan pemberdayaan masyarakat perlu dilandasi oleh strategi kerja yang tepat demi keberhasilannya mencapai tujuan yang diinginkan. Kegiatan pemberdayaaan dilakukan melalui tiga tahap mulai dari tahap penyadaran, pengkapasitasan hingga pada tahap pendayaan. Hal tersebut juga yang menjadi basis strategi pemberdayaan pada Gapoktan Rukun Agawe Sentosa Pekon Wonoharjo dalam meningkatkan kesejahteraan ekonomi masyarakat.